2008
DOI: 10.2215/cjn.03190807
|View full text |Cite
|
Sign up to set email alerts
|

DDAVP Is Effective in Preventing and Reversing Inadvertent Overcorrection of Hyponatremia

Abstract: Background and objectives: Adherence to therapeutic guidelines for the treatment of hyponatremia becomes difficult when water diuresis emerges during therapy. The objective of this study was to assess the effectiveness and safety of desmopressin acetate as a therapeutic agent to avoid overcorrection of hyponatremia and to lower the plasma sodium concentration again after inadvertent overcorrection.Design, setting, participants, & measurements: Retrospective chart review was conducted of all patients who were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(93 citation statements)
references
References 15 publications
0
87
0
6
Order By: Relevance
“…38 Rapid recognition of ODS could aid in treatment because prompt reduction in serum sodium levels can benefit patients in the early stages of the disease. 39,40 Therefore, we investigated whether the early neurologic manifestations and fatal outcome in ODS could be predicted on the basis of serum S100B levels. Compared with asymptomatic rats, we showed that 24 hours after serum sodium correction, S100B was significantly higher in rats undergoing early neurologic manifestations (within 2 days postcorrection).…”
Section: Serum Levels Of the Astrocytic Protein S100b Predict Inadvermentioning
confidence: 99%
“…38 Rapid recognition of ODS could aid in treatment because prompt reduction in serum sodium levels can benefit patients in the early stages of the disease. 39,40 Therefore, we investigated whether the early neurologic manifestations and fatal outcome in ODS could be predicted on the basis of serum S100B levels. Compared with asymptomatic rats, we showed that 24 hours after serum sodium correction, S100B was significantly higher in rats undergoing early neurologic manifestations (within 2 days postcorrection).…”
Section: Serum Levels Of the Astrocytic Protein S100b Predict Inadvermentioning
confidence: 99%
“…When this formula predicts a rather inappropriate increase of serum sodium levels proper modifications of the infused solutions should be performed (f.e. administration of hypotonic sodium solutions or even 5% dextrose in water, or simultaneous administration of desmopressin (a synthetic vasopressin) to prevent and reverse inadvertent overcorrection of hyponatremia [20,21] .…”
mentioning
confidence: 99%
“…Thus far, re-lowering serum sodium is the most beneficial treatment when the initial osmotic injury has already occurred. 6,[33][34][35] Our results suggest that, in clinical practice, early administration of minocycline might have a role in preventing neurologic damage in hyponatremic patients who underwent rapid correction of their sodium deficit. Nevertheless, re-lowering of serum sodium should remain the treatment of choice when a toxic gradient is achieved until further work is done to fully explore the possibilities of minocycline in management of rapid correction of chronic hyponatremia in terms of the minimal effective dose and possible combination with re-lowering of serum sodium.…”
Section: Discussionmentioning
confidence: 69%